CORONARY ARTERY DISEASE PATTERN: A COMPARISION AMONG DIFFERENT AGE GROUPS - Khan, Hazrat Ullah; Khan, Mati Ullah; Noor, Muhammad Munir; Hayat, Umer; Alam, Muhammad Adeel (Journal of Ayub Medical College Abbottabad, 2014)
Background: Angiographic studies have shown that the extent of disease and severity is less in younger population with comparatively fewer number of coronary arteries affected than that of older age groups. This study was conducted to compare the pattern of coronary artery disease (CAD) in young adults under 40 years and those more than 40 years of age with significant coronary artery disease on coronary angiography. Methods: This cross-sectional study was conducted in Angiography Laboratory of Punjab Institute of Cardiology, Lahore, from 1st April, 2013 to 1st April, 2014. Patients from Angiography Laboratory of Punjab institute of cardiology Lahore were enrolled in the study. A Joint Committee of consultants reported the coronary lesions (stenosis). Single vessel disease (SVD), Double vessel disease (DVD) and Tripple vessel disease (TVD) was noted down. Results: Out of total 400, patients of age ‰¤40 years (Group-A) were 48 (12%) and >40 years (Group-B) were 352 (88%). There were 77% male patients and 22.5% females. Mean age of patients was 52.78±10.02. Significant CAD was present in 48 (10.75%) patients of Group-A and in 306 (76.5%) patients of group-B. Frequency of SVD, DVD and TVD in Group-A was 24 (50%), 10 (20.8%) and 9 (18%) respectively while frequency of SVD, DVD and TVD in group-B was 98 (27%), 88 (25%) and 120 (34%) respectively with p-value of 0.002, 0.53 and 0.03 among SVD, DVD and TVD between the two groups. Conclusion: Young (age <40 years) patients who have coronary artery disease, have less extensive coronary artery disease, with a high incidence of angiographically normal vessels and relative paucity of left main coronary arterial involvement. Keywords: Pattern, coronary artery disease, myocardial infarction, young